THE IMPROVEMENT of STUDENT INTELECTUAL AND PARTICIPATORY SKILL through PROJECT CITIZEN MODEL IN CIVIC EDUCATION CLASSROOM - Adha, Muhammad Mona; Yanzi, Hermi; Nurmalisa, Yunisca (International Journal Pedagogy of Social Studies, 2018)
The use of learning models in classroom civic education becomes substantive. Improving student learning outcomes and motivation in the classroom is the main goal of the project citizen model. The learning steps in this model invite students to be active, think critically, be able to work together, be creative, and get an effective learning experience. The control class and the experimental class are subject to quasi experiment. The results show that there is a significant increase in students' intellectual and participatory skills in students who use project citizen models. The creativity and ability of the teacher to use the learning model project citizen has implications for student motivation and open classroom climate. The implication of this research is that building a democratic society requires education so that its citizens can criticize and understand existing problems. Thus the civic education will produce a democratic education by giving birth to a smart, open, independent and democratic future generation.